Isolation and characterization of lactic acid bacteria derived from fermented dairy products - Rahman, Abdur; Akter, Mofassara; Rahman, Ashikur; Biswas, Lita; Sultana, Mst Tasmim; Islam, Md Saiful; Asaduzzaman, Md (Asian-Australasian Journal of Food Safety and Security, 2026)
Lactic acid bacteria (LAB) are important in dairy food fermentation, which have beneficial health properties. This study aimed to isolate, characterize, and identify LAB from fermented dairy products such as dahi, borhani, matha, lassi, and cheese, and to evaluate their antibiotic susceptibility patterns. The study was conducted from March 2022 to August 2023. Bacteria were selected based on colony morphology on de Man, Rogosa and Sharpe (MRS) agar, Gram staining, biochemical tests, and molecular methods. All isolates were tested for sugar fermentation and growth at various temperatures and salt levels. Identification was confirmed through PCR and 16S rDNA sequencing. While all isolates tolerated low concentrations of NaCl (≤5%), none could survive high concentrations (≥6%). They successfully fermented glucose, sucrose, and lactose. Antibiotic susceptibility testing showed sensitivity to gentamicin, ciprofloxacin, tetracycline, and ceftriaxone in all isolates. The species identified included Lactobacillus rhamnosus from dahi, lassi, and matha, as well as Lactobacillus fermentum from cheese, both of which are recognized as probiotic strains. The findings suggest these two antibiotic-sensitive LAB species are suitable for use in fermented dairy product formulations. These results provide a scientific basis for developing safe, standardized starter cultures to enhance the quality and safety of fermented dairy products in Bangladesh. Asian Australas. J. Food Saf. Secur. 2026, 10(1), 43-50